2x2 − 2z4 + y2 − x2 + z4 if x = −4, y = 3, and z = 2.
1 answer:
answer: 9
Step-by-step explanation:
x = - 4; y = 3; z = 2;2 x² - 2 z^4 + y² - x² + z^4 = = 2 * (-4)² - 2 * 2^4 + 3² - ( -4)² + 2^4 == 2 * 16 - 2 * 16 + 9 - 16 + 16 = = 32 - 32 + 9 - 16 + 16 = 9
You might be interested in
Given the expression:
![\sqrt[4]{ \frac{24x^{6}y}{128x^{4}y^{5}}}](https://tex.z-dn.net/?f=%5Csqrt%5B4%5D%7B%20%5Cfrac%7B24x%5E%7B6%7Dy%7D%7B128x%5E%7B4%7Dy%5E%7B5%7D%7D%7D)
Simplifying:
![\sqrt[4]{ \frac{3x^{2}}{16y^{4}}}](https://tex.z-dn.net/?f=%5Csqrt%5B4%5D%7B%20%5Cfrac%7B3x%5E%7B2%7D%7D%7B16y%5E%7B4%7D%7D%7D)
Then the answer is:
It would be 7 on the side and then 2/6
Answer:
They are equivalent
Step-by-step explanation:
Since 3.75 divided by 5 is .75 that means that 6 divided by 8 would have to also be .75 which, if you divide it, it is.
How to write an equivalent expression for n time a using o
Answer:
50cm
Step-by-step explanation:
oh apdiya I just wanted to let you